THE EFFECT OF ADDING FLY ASH AND GLASS POWDER ON THE COMPRESSION STRENGTH OF CONCRETE - Sandi Indratama; Agung Sumarno; Syafwandi Syafwandi; Agyanata Tua Munthe (Neutron, 2023)
The purpose of this study was to determine the effect of the use of fly ash waste and glass powder on the compressive strength of concrete. 17.5% at the age of 3 days, 7 days, 14 days, and 28 days. for the specimens used measuring with a diameter of 10 cm and a height of 20 cm as many as 36 test samples by making variations of the day as many as 3 samples of the test object, After testing the compressive strength of concrete, the compressive strength of the characteristic concrete with the addition of 7% fly ash and glass powder 5%, the maximum compressive strength at the age of 7 days was 23.35 Mpa, the age of 14 days was 28.93 Mpa, and the age of 28 days was 33.85 Mpa. These results exceed the value of the compressive strength of normal concrete characteristics and indicate that fly ash and glass powder increase the compressive strength of concrete. There is a strong influence from the addition of fly ash and glass powder with variations in the addition and certain age of concrete